(untitled) (Shiksha Shastra Saurabh, 2025)
The use of Artificial Intelligence (AI) has been increasingly using in different areas, including teaching, learning and professional development. In this regard, this study explores the opportunities and challenges faced by secondary-level English teachers while integrating AI tools, like ChatGPT and MagicSchool AI for their professional growth. A qualitative research design was adopted. Four secondary-level English teachers, two from community and two from private schools of Kathmandu district having at least one-year experiences of using AI tools were purposively selected as the sample. Data were collected using semi-structured interviews. Teachers’ narratives were transcribed and analysed thematically. The findings from the narratives show that teachers get many opportunities, including becoming the best learning partner, material creation and designing, workload reduction, and interesting and engaged classroom techniques while integrating AI tools in developing their teaching profession. However, they faced some challenges, such as inadequate equipment and infrastructure, incomplete technological knowledge on the part of teachers, and over-dependency. Importantly, AI tools have high potential for teachers’ professional development and transformative pedagogy. So, technological training for teachers, management of the required infrastructure and equipment, and proper policy formation are mandatory to promote AI tools in sustainable integration for teachers’ capacity building.